The transdermal cream of Formestane anti-breast cancer by controlling PI3K-Akt pathway and the tumor immune microenvironment - Gao, Lanyang; Zhu, Lei; Shen, Chen; Hou, Xiaoming; Chen, Youyou; Zou, Linglin; Qiang, Huiyan; Teichmann, Alexander T.; Fu, Wenguang; Luo, Yao (Frontiers in Immunology, 2023)
Treatment of ER+ breast cancer with intramuscular formulation of Formestane (4-OHA) shrinks the tumor within weeks. Since the tedious way of intramuscular administration and side effects are not suited for adjuvant treatment, Formestane was withdrawn from the market. A new transdermal formulation of 4-OHA cream may overcome the defects and retain the effect of shrinking the breast cancer tumor. However, the effects of 4-OHA cream on breast cancer need further confirmatory studies. In this work, in vivo, the influence of 4-OHA cream on breast cancer was evaluated using the mode of 7,12-dimethylbenz(a)anthracene (DMBA) induced rat mammary cancer. We explored the common molecule mechanisms of action of 4-OHA cream and its injection formulation on breast cancer. The results showed that the cream substantially reduced the entire quantity, size, and volume of tumors in DMBA-treated rats consistent with 4-OHA injection. RNA-sequencing-based transcriptome analysis and several biochemical experiments indicated that there were comprehensive signals involved in 4-OHA antitumor activity, such as ECM-receptor interaction, focal adhesion, PI3K-Akt signaling pathway, and proteoglycans in cancer. In addition, we observed that both 4-OHA formulations could enhance immune infiltration, especially CD8+ T cells, B cells, natural killer cells, and macrophages infiltration, in the DMBA-induced mammary tumor tissues. The antitumor effects of 4-OHA partly depended on these immune cells. In summary, these results suggested that 4-OHA cream may provide a new way for neoadjuvant treatment of ER+ breast cancer.